Internalisasi Pesan Dakwah pada Tradisi Keleman dalam Perspektif Interaksi Simbolik - Muchamad Wildanil Mubarok Wildanil Mubarok (IAI Darussalam, 2026)
This reseach explores the internalization of the message of da'wah in the keleman tradition from a symbolic interaction perspective. Keleman is a local tradition that reflects a blend of culture and Islamic teachings, especially in the farming community in Tambakrejo Hamlet. This study aims to identify how the message of da'wah conveyed by this keleman tradition is in accordance with the 3 patterns of George Herberd Mead's symbolic interaction theory, namely mind, self, and society. This reseach uses a qualitative method with a case study approach, data collected through interviews, observations, and literature studies. The findings show that the internalization of the message of da'wah in the keleman tradition can occur due to the interaction of the Tambakrejo community that occurs both verbally and non-verbally. The result is that the message of da'wah arises from the interaction of the community: (a) Mind, which changes the keleman tradition from being carried out at the grave to being moved to the hamlet hall, (b) Self, which views the symbols in the keleman tradition in the meaning of each individual, (c) Society, which gives meaning to the keleman tradition as a hope that the planting process will be smooth without any obstacles.